A history of Islamic societies - Lapidus, Ira M. (Cambridge University Press, 2014)
"This third edition of Ira M. Lapidus's classic A History of Islamic Societies has been substantially revised to incorporate the insights of new scholarship and updated to include historical developments in the first decade of the twenty-first century. Lapidus's history explores the beginnings and transformations of Islamic civilizations in the Middle East and details Islam's worldwide diffusion to Africa; Spain; Turkey and the Balkans; Central, South and Southeast Asia; and North America, situating Islamic societies within their global, political, and economic contexts. It accounts for the impact of European imperialism on Islamic societies and traces the development of the modern national state system and the simultaneous Islamic revival from the early nineteenth century to the present. This book is essential for readers seeking to understand Muslim peoples"--